Biology and Culture of Percid Fishes Principles and Practices - Kestemont, Patrick.; Kestemont, Patrick.; Dabrowski, Konrad.; Dabrowski, Konrad.; Summerfelt, Robert C.; Summerfelt, Robert C. (Springer Netherlands : Imprint: Springer, 2015)
This extensive work focuses on an important group of temperate freshwater fish, approaching the topic from the perspectives of both biology and aquaculture. It compiles the latest research on fish belonging to the Percidae family and describes in detail all biological aspects relevant to the culture of different species, including ecology, reproductive physiology, feeding and nutrition, genetics, immunology, stress physiology and behavior. It also considers commercial fish production and fish farming topics, such as protocols for induction of gonad maturation, spawning, incubation and larval rearing. Expert contributors not only provide a critical peer review of scientific literature but also original research data, and identify effective practical techniques. The book features chapters on systematics, ecology and evolution, on development, metabolism and husbandry of early life stages and on growth, metabolism, behavior and husbandry of juvenile and grow-out stages. Furthermore, the authors consider genetic improvement and domestication, as well as diseases and health management, crucial to the readers' understanding of these fish and how they can be cultured. Both researchers of percid fish biology and aquaculture professionals who are considering intensive and pond culture of percid fishes will value this timely and comprehensive handbook.